Quality of Life at Work of Police Officers, Metropolitan Police Division 6 - แก้วทินกร, พันตำรวจโทกิตติ; รัชตพิบุลภพ, พิชิต (Journal of Humanities and Social Sciences, Rajapruk University, 2020)
This research aimed to investigate and compare the levels of quality of life at work of police officers, Metropolitan Police Division 6. The sample used in this research included 349 police officers, Metropolitan Police Division 6. The tool of the research was questionnaire. The statistics used in data analysis included frequency, percentage, average, standard deviation, t-test, and One-way ANOVA. The research findings revealed that the quality of life at work of police officers, Metropolitan Police Division 6 overall was at fair level. The consideration of each dimension revealed that the average of all dimensions was at fair level. The study was divided into seven dimensions namely compensation, work environment, opportunity for self-development, career advancement and security, work with society, democracy within organization, and balance between working and personal lives. The study findings of the comparison of the levels of quality of life at work of police officers Metropolitan Police Division 6 classified by personal status, revealed that the levels of quality of life at work of police officers, Metropolitan Police Division 6 classified by gender, age, marital status, education, current department, duration of work, and monthly income, there was no difference in the opinions.